Global and Regional Evolution of Economic Communication Research (1960–2024): Systematic Review and Bibliometric Analysis - Baehaqi; Mohammad Najib Roodhi; Muhammad Mujahid Dakwah (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study provides the first longitudinal and global mapping of the evolution of Economic Communication from 1960 to 2024 by combining a systematic literature review (PRISMA) with bibliometric analysis (VOSviewer) of 117 Scopus-indexed articles. The findings reveal that the field has transformed from fragmented, discipline-specific studies into an interdisciplinary domain shaped by digital transformation, globalization, and shifting policy agendas. Five interconnected thematic clusters were identified—macroeconomic growth, sustainability communication, ICT–FDI linkages, digital inequality, and crisis-related messaging—highlighting communication’s function as a governance tool, an enabler of inclusive participation, and a driver of resilience. By embedding these clusters within frameworks such as Risk Communication Theory, the Digital Divide Framework, and Global Value Chain Theory, the study advances conceptual clarity and situates communication at the center of development and policy discourse. Its contribution lies in offering a theory-anchored synthesis that bridges structural mapping with interpretive insight, while foregrounding emerging contributions from the Global South. Limitations include reliance on Scopus and English-language publications, which risks selection and language bias. Future research should expand to multi-database and multilingual corpora, integrate mixed-method approaches, and examine AI-mediated communication to address inequalities and institutional trust in diverse contexts.